Keragaman Gen Heat Shock Protein 70 pada Ayam Kampung, Ayam Arab, dan Ayam Ras (POLYMORPHISMS OF THE HEAT SHOCK PROTEIN 70 GENE IN KAMPONG, ARABIC, AND COMMERCIAL CHICKENS) - Tamzil, Mohamad Hasil; Noor, Ronny Rachman; Manalu, Wasmen; Sumantri, Cece (Jurnal Veteriner, 2013)
The aim of the research was to identify the polymorphisms of HSP-70 gene of kampong, Arabic, andcommercial chickens. The study used whole blood samples taken from the branchial vein at the age of 12weeks from a group of chickens that were kept since DOC. Kampong chickens DOC were obtained byhatching the eggs that were collected from lowlands, medium and high altitude areas in Lombok island,while the Arabic chickens DOC were obtained from farmer. DOC of commercial chickens were purchased atthe poultry shop. The genotyping results using PCR-SSCP analysis showed that kampong and arabicchickens were polimorphic, while commercial chickens were  classified as monomorphic. Kampong chickenshad seven genotypes of HSP-70, namely AA, AB, AC, CC, AD, DD, and BC.  The AD genotypes had thehighest frequency, whereas in arabic chickens had six genotypes, namely AA, AB, AC, CC, AD and BC,which AC genotype had the highest frequencies.  However, the commercial chickens contain only onegenotype which was DD. There were three polymorphic sites found in amplificated area, namely AÆGmutation at site 617, AÆG mutation at site 628, GÆC mutation at site 646,  CÆT mutation at site 661,AÆG mutation at site 699, GÆC mutation at site 754, and AÆG mutation at site 792.  Mutations at sites628, 646 and 661 were considered as silent mutation. HSP-70 gene in kampung and arabic chickenpopulation in this study was in equilibrium. The value of Ho, He, and PIC of kampung and arabic chickenswere not different.
Keywords: polymorphism, HSP-70, native chicken, PCR-SSCP